2022
DOI: 10.1186/s13098-022-00803-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes mellitus on outcomes of patients with sepsis: an updated systematic review and meta-analysis

Abstract: Background The effect of concurrent diabetes on the outcome of sepsis is not conclusively known. A meta-analysis published in 2017 indicated that diabetes did not influence the mortality of patients with sepsis but increased the risk of acute renal injury. In view of publication of several new studies in recent years, there is a need for updated evidence. Methods A systematic search was conducted using the PubMed, Scopus, Embase, and Google Scholar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 54 publications
4
20
0
1
Order By: Relevance
“…The mechanisms that lead to glucose dysregulation are complex. Elevated blood glucose levels tend to reduce membrane fluidity, which impedes polymorphonuclear leukocyte (PMN) function, leading to reduced phagocytosis, intracellular killing, suboptimal migration, and chemotaxis ( 20 , 36 , 37 ). In addition, the neuroendocrine stress response can increase adrenal cortex secretion by 10 times, including excessive glycogenolysis, gluconeogenesis, and insulin resistance ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms that lead to glucose dysregulation are complex. Elevated blood glucose levels tend to reduce membrane fluidity, which impedes polymorphonuclear leukocyte (PMN) function, leading to reduced phagocytosis, intracellular killing, suboptimal migration, and chemotaxis ( 20 , 36 , 37 ). In addition, the neuroendocrine stress response can increase adrenal cortex secretion by 10 times, including excessive glycogenolysis, gluconeogenesis, and insulin resistance ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, numerous studies have demonstrated an association between failure to control hyperglycemia and adverse outcomes in patients in the intensive care unit (ICU), including death, nosocomial infection, wound complications, prolonged ICU stay, and an increased incidence of critical illness neuropathy ( 19 ). Acute hyperglycemia is an independent risk factor for in-hospital mortality in critically ill patients with sepsis ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, Although the severities of infection, circulatory dysfunction, and IECs damage were milder, neither a slighter compromised intestinal barrier integrity nor a better outcome was achieved in HbA1c ≥ 6.5% Group. Since gut dysbiosis and compromised intestinal barrier integrity have been induced by hyperglycemia before the onset of critical illness [ 10 , 12 ], for those patients with pre-existing hyperglycemia, the co-effect of hyperglycemia and critical illness will result in more severe compromised intestinal barrier integrity, bacterial translocation, and finally worse outcome [ 4 , 5 ]. Therefore, we suggested that the compromised intestinal barrier integrity might be responsible for the poor prognosis in critically ill patients with pre-existing hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some anti-diabetic agents with the capability of improving intestinal barrier integrity can bring advantages in the management of critical illness [30]. Given that hyperglycemia, irrespective of the diabetes status, is associated with poor prognosis in critically ill patients [4,5], the role of compromised intestinal barrier integrity in critically ill patients with pre-existing hyperglycemia theoretically answers the question why it is important to control hyperglycemia. This study had some limitations.…”
Section: Perspective: the Control Of Hyperglycemia In Critical Illnes...mentioning
confidence: 99%
See 1 more Smart Citation